A Little AXER ABC: ATP, BiP, and Calcium Form a Triumvirate Orchestrating Energy Homeostasis of the Endoplasmic Reticulum. (May 2020) - Zimmermann, Richard; Lang, Sven
Pioneering work in the 1990s started to address an interesting question. How is the main cellular energy source, adenosine triphosphate (ATP), imported into the mammalian endoplasmic reticulum (ER)? Despite its high-energy demand, large volume, and structural as well as functional complexity, the ER harbors no intricate system for ATP synthesis or regeneration. Although the original biochemical reconstitution approaches established hallmarks of the ATP transport into the ER including nucleotide selectivity, affinity, and antiport mode, the more recent live-cell imaging methods employing sensitive, localized molecular probes identified the elusive ATP/adenosine diphosphate (ADP) exchanger. According to its selectivity and localization, the identified SLC35B1 protein was rebranded AXER. Here, we discuss the identification and regulation of AXER plus the cytosolic partners (AMP-activated protein kinase, AMPK) and subcellular structures (mitochondrial–ER contact sites, MERCs) acting in concert with it to orchestrate energy homeostasis of the mammalian ER. Furthermore, we combine the two seemingly controversial regulatory mechanisms (lowER and CaATiER) in a unifying hypothesis.